Dietary Patterns and Oxidative Stress in a Population of Women with Breast Cancer in the North-Western Regions of Algeria (Saida and El-Bayadh) - Halla, Noureddine; Boucherit, Kebir; Hachem, Kadda; Asmouni, Amouria; Derrab, Hanane; Boucherit-Otmani, Zahia (Journal of Drug Delivery and Therapeutics, 2020)
Objective: The aim of this work is the study of risk factors for breast cancer in a population of women in the north-western regions of Algeria (Saida and El-Bayadh) Methodology: A case-control study was carried out on 40 women including 20 cancerous women and 20 control women, in order to determine the dietary patterns and general characteristics of the population studied and to compare the hematological and biochemical parameters, and markers of oxidative/antioxidant status between control women and breast cancer women. Results: The results obtained show that there is no significant difference in the average age however the body mass index was significantly increased in cancer women, revealing overweight (p <0.05), compared to control women. The marital status of the target population is predominantly a married woman status and the level of education shows a relatively low level in breast cancer cases compared to women controls. The illiteracy rate is exceptionally high in cancer women compared to controls (35% versus 20%). In addition, the levels of glucose, creatinine, HDL and ALAT are similar between the two groups of women. The contents of urea, cholesterol, triglyceride, LDL, ASAT, malondialdehyde and uric acid are significantly increased in women with breast cancer compared to women controls. But the vitamin C content is significantly reduced in cancer women compared to control women. Conclusion: We conclude from this study that there is an association between breast cancer and lipid alteration, oxidative stress, age, increase in BMI, socio-demographic data, professional situation, age, means of menstruation and menopause, and ultimately the lifestyle. All these factors are risk factors for breast cancer in the region of Saida and El-Bayadh. Keywords: Breast Cancer, Risk Factors, Dietary Patterns, Oxidative Stress.